The Effect Of Commitment And Organizational Culture On The Performance Of Civil Servants In The Department Of Education And Culture Of Banda Aceh City - Muhammad, Muhammad; Nurbismi, Nurbismi; Tarmizi, Tarmizi; Zahwa, Putri (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
This study aims to analyze the influence of commitment and organizational culture on the Performance of Civil Servants at the Banda Aceh City Education and Culture Office. The research sample was 59 civil servants at the Banda Aceh City Education and Culture Office using census techniques. Data analysis used statistical analysis of correlation and multiple regression models with the help of SPSS 25 Software. The results of the analysis showed that simultaneously there was an influence between commitment and organizational culture on Civil Servant Performance. The results of the F test obtained the F count> F table or (4.269> 2.77) and the significant test that the p value was 0.001 < p set at 0.05 which means significant. The partial test results show that: 1. Commitment has an effect on Civil Servant Performance with T count 3.896> T table 1.672 and p value 0.004 < from p 0.05 means significant. 2. Organizational culture influences the performance of civil servants with Tcount 2.253> Ttable 1.672 and p value 0.008 <from p 0.05 means significant. Based on the results of this study, it is recommended for leaders to maintain and improve the commitment of existing employees, because its partial and simultaneous influence on performance is significant, meaning that so far the existing commitment has been good and improves performance.